Effects of Corporate Social Responsibility on consumer brand loyalty - Rivera, José Javier; Bigne, Enrique; Curras-Perez, Rafael (Review of Business Management, 2019)
Purpose – This paper analyses the influence of CSR associations on brand loyalty. We propose a theoretical model that includes the mediating role of brand awareness, brand attitude and customer satisfaction in the effect of CSR on loyalty, measured as a second-order reflective construct. Design/methodology/approach – We propose a theoretical model estimated via the analysis of covariance structures using EQS 6.1. Data were obtained using an online survey of 351 Spanish sportswear consumers. Findings – This study illustrates that CSR associations have a direct, positive influence on loyalty, and an indirect influence through their positive effect on brand awareness and consumer satisfaction. Brand attitude does not appear to play a significant role in the influence of CSR on loyalty. Originality/value – We study the effect of CSR associations, brand awareness, satisfaction, and brand attitude as drivers of brand loyalty, conceived as a reflective second-order construct with four dimensions: attitudinal loyalty, purchase intention, expenditure level and intention to recommend. It is important to construct relational marketing strategies that integrate CSR with consumer orientation using the three dimensions of the model validated in the study: brand awareness, satisfaction and brand attitude.